The Productivity Consequences of Two Ergonomic Interventions - Kelly DeRango; III Ben Amick; Michelle Robertson; Ted Rooney; Anne Moore; Lianna Bazzani (W.E. Upjohn Institute for Employment Research, 2003)
Pre- and post-intervention data on health outcomes, absenteeism, and productivity from a longitudinal, quasi-experimental design field study of office workers was used to evaluate the economic consequences of two ergonomic interventions. Researchers assigned individuals in the study to three groups: a group that received an ergonomically designed chair and office ergonomics training; a group that received office ergonomics training only; and a control group. The results show that while training alone has neither a statistically significant effect on health nor productivity, the chair-with-training intervention substantially reduced pain and improved productivity. Neither intervention affected sick leave hours.
Keywords: I1; J0; J8; M5; 330; ergonomics; chair; pain; DeRango